Epistemologi Hermeneutika Hadis Kontemporer: Dialektika Otoritas Teks dan Kontekstualisasi dalam Pemikiran Khaled M. Abou El-Fadl dan Yusuf al-Qaradawi - Nur Annisa Istifarin; Masruhan Masruhan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The development of contemporary hadith studies has demonstrated a paradigmatic shift from textual approaches toward more contextual and hermeneutical perspectives. In this regard, Khaled M. Abou El-Fadl and Yusuf al-Qaradawi represent two influential scholars who offer distinct epistemological models for understanding hadith. This study aims to analyze and compare the epistemology of hadith hermeneutics developed by both scholars, particularly concerning the relationship between textual authority and contextualization. Employing a qualitative method through library research and comparative analysis, this study examines the primary works of the two figures. The findings reveal that Khaled M. Abou El-Fadl advances a negotiative hermeneutics that views meaning as the product of interaction among the author, the text, and the reader, thereby preventing authoritarian interpretations. In contrast, Yusuf al-Qaradawi develops a hadith interpretation framework grounded in maqāṣid al-sharī‘ah, asbāb al-wurūd, and the distinction between legislative (tashrī‘iyyah) and non-legislative (ghayr tashrī‘iyyah) Sunnah to maintain the relevance of hadith across changing social contexts. The study finds that the primary difference between the two scholars lies in their respective conceptions of textual authority and the scope of contextualization, although both seek to ensure the continued relevance of hadith in modern Muslim societies. This research contributes to contemporary hadith hermeneutics by providing a comparative mapping of critical and maqāṣid-oriented interpretive models within hadith studies.